Pengawasan Pemerintah Daerah terhadap Pengelolaan Limbah B3 Internal Rumah Sakit - Fikri Naufal Uyun; Frency Siska; Nurul Chotidjah (Jurnal Riset Ilmu Hukum, 2022)
Abstract. There is news about the disposal of medical waste at the Temporary Waste Disposal Site (TPS) belonging to the Ciamis District General Hospital. This study uses a normative juridical research method. Research data is collected by examining theories, concepts, legal principles and legislation. As well as data analysis obtained both from literature studies and from field research will be analyzed qualitatively. The results of this study indicate that in its implementation the Ciamis District Hospital is guided by Law number 32 of 2009 concerning environmental protection and management. The parties involved are from the PRKPLH Service and the vendors who have been provided by the local government, while the hospital involved is the sanitarian section. There are still violations of regulations, meaning that the Government's Governance for the Environment at the Ciamis District Hospital has not been effective. The Ciamis District Hospital should always improve supervision in the management of B3 waste by providing direction or understanding about the importance of using waste symbols so that medical and non-medical waste is not mixed. It is recommended that the Ciamis Regency Government emphasize more on the agency by creating a B3 and B3 Waste management team at the Ciamis Regency Hospital to be more responsible in carrying out their duties so that monitoring activities can run effectively and efficiently. Abstrak. Adanya pemberitaan pembuangan limbah medis di Tempat Pembuangan Sampah (TPS) Sementara milik Rumah Sakit Umum Daerah Kabupaten Ciamis. Penelitian ini menggunakan metode penelitian yuridis normative. Data penelitian dikumpulkan dengan cara menelaah teori-teori, konsep-konsep, asas-asas hukum serta peraturan perundang- undangan. Serta analisis data yang diperoleh baik dari studi kepustakaan maupun dari penelitian lapangan akan dianalisis secara kualitatif. Hasil penelitian ini menunjukkan bahwa dalam pelaksanaannya RSUD Kabupaten Ciamis berpedoman pada Undang-Undang nomor 32 Tahun 2009 tentang perlindungan dan pengelolaan lingkungan hidup. Pihak yang ikut terlibat yakni dari Dinas PRKPLH dan pihak vendor yang sudah disediakan oleh PEMDA sedangkan dari pihak Rumah Sakit yang terlibat adalah bagian sanitarian. Masih adanya pelanggaran terhadap peraturan mengartikan bahwa Tata kelola Pemerintah terhadap Lingkungan Hidup di RSUD Kabupaten Ciamis belum Efektif. Sebaiknya pihak RSUD Kabupaten Ciamis selalu meningkatkan pengawasan dalam pengelolaan limbah B3 dengan memberikan arahan atau pemahaman tentang pentingnya pengunaan simbol-simbol limbah agar tidak tercampur limbah medis dengan non-medis. Sebaiknya pihak Pemerintah Kabupaten Ciamis lebih mempertegas kepada instansi dengan membuat tim pengelolaan B3 dan Limbah B3 di RSUD Kabupaten Ciamis agar lebih bertanggung jawab dalam melakukan tugasnya agar kegiatan monitoring dapat berjalan dengan efektif dan efisien.